Law in everyday Japan sex, sumo, suicide, and statutes - West, Mark D., 1968- (Chicago, Ill. : University of Chicago Press, 2005)
A compilation of case studies centred on seven everyday themes from karaoke-based noise complaints to debt-induced suicide this book offers a portrait of the way law intermingles with social norms, historically ingrained ideas, & cultural mores in Japan.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Law -- Japan; Law and economics; Sociological jurisprudence; Law; Japan; Jurisprudence & general issues; Arbitration, mediation & alternative dispute resolution